An introduction to non-traditional security studies: a transnational approach - Caballero-Anthony, Mely (SAGE, 2016)
Understanding non-traditional security / Mely Caballero-Anthony -- On security / Mely Caballero-Anthony -- Actors and stakeholders / Alistair D.B. -- Conflict and community security / Mely Caballero-Anthony -- Poverty and economic security / Bob S. Hadiwinata -- Environmental security / J. Jackson Ewing -- Food security / Paul Teng and Jonatan Lassa -- Energy security / Daojiong Zha -- Water security / Marcus DuBois King -- Health security / Simon Rushton -- Migration and movements of people / Melissa Curley -- Transnational crime / David Capie